Hambatan Pemberian ASI Eksklusif Pada Bayi Usia 0-6 Bulan - Asnidawati Asnidawati; Syahrul Ramdhan (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Abstract. Introduction; the rate of exclusive breastfeeding has been made by various international and national efforts, however, the coverage rate for exclusive breastfeeding has not reached the predetermined target. know the causes or barriers to exclusive breastfeeding in infants aged 0-6 months. Method; data were obtained from various electronic databases using google scholar, scientific director, and published using the keywords